Analysis of serum vitamin C and nitric oxide in children with septic shock - Yunarto, Yuliana; Ratih, Dewi; Wistiani, Wistiani (Indonesian Pediatric Society, 2023)
Background Imbalance of oxidants and antioxidants contributes to the sepsis process. Nitric oxide (NO) is an oxidant produced abundantly during sepsis and plays key role in the pathogenesis of hypotension in septic shock. Vitamin C functions as a potent antioxidant to scavenge free radicals, reduce endothelial permeability, cellular apoptosis, and endogenous vasopressor synthesis cofactor. Vitamin C prevents excessive production of NO by suppressing inducible nitric oxide synthase (iNOS) expression. Objective To analyze for a possible correlation between serum vitamin C and NO levels in children with septic shock. Methods This cross-sectional study was conducted in Dr. Kariadi Hospital, Semarang, Central Java, Indonesia. A total of 40 children with septic shock aged 1 month - 18 years were consecutively recruited. Serum vitamin C and serum NO levels were measured using colorimetric assay kits. Results Of 40 children with septic shock, 21 (52.5%) were male, 21 (52.5%) were undernourished, 25 (62.5%) were on mechanical ventilators, and 10 (25%) required more than one vasoactive agent. Blood gas analysis revealed acidosis in 31 (77.5%) children. Subjects’ median age was 20 months (2-214 months). Mean serum vitamin C level was 7.35 (SD 2.723) µg/mL and mean serum NO was 47.25 (SD 19.278) µmol/L. There was no significant correlation between serum vitamin C levels and serum NO in children with septic shock (r=0.056; P=0.732). Conclusion Serum vitamin C levels and serum NO has no correlation in children with septic shock.